ACTive: Fighting Stress with Acceptance and Commitment - Dewi, Ni Putu Laksmi; Yudiarso, Ananta (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Mental health is still a special concern for everyone. The pandemic situation that has occurred almost throughout the world in the last few years has had an emotional impact, problems with concentration, stress, and even depression. This research was conducted to determine the effectiveness of ACT in reducing stress by using previous literature from 10 international research journals that are relevant to the research variables. The number of participants in this study was 1970 people who were divided into two groups. Experimental group (n=993 participants) and control group (n=977 participants). This research utilizes data from the number of participants (n), average value (mean), and standard deviation (SD) to find the effect size obtained from random effects. The meta-analysis used in this research uses the Egger's Regression method. Calculations use Jamovi software version 2.2.5.0 to carry out the data calculation process. The research results show that the random effect model value is -1.24 (95% CI= -2.249 to -0.227). The results of the p value = <0.001 with I² (inconsistency) = 98.67%. Based on the results of the meta-analysis test, it can be concluded that ACT shows a large effect size. This shows that ACT intervention is effective in reducing a person's stress. Acceptance and Commitment Therapy (ACT) can be used effectively and has a significant impact on reducing stress.Kesehatan mental masih menjadi perhatian khusus bagi setiap orang. Situasi pandemi yang terjadi hampir diseluruh dunia dalam beberapa tahun terakhir menimbulkan dampak secara emosional, masalah konsentrasi, stres, hingga depresi. Penelitian ini dilakukan untuk mengetahui efektifitas ACT untuk menurunkan stres dengan menggunakan literatur terdahulu dari 10 jurnal penelitian international yang relevan dengan variabel penelitian. Jumlah partisipan pada penelitian ini adalah 1970 orang yang dibagi menjadi dua kelompok. Kelompok eksperimen (n=993 partisipan) dan kelompok kontrol (n=977 partisipan). Penelitian ini memanfaatkan data dari jumlah partisipan (n), nilai rata-rata (mean), dan standar deviasi (SD) akan menemukan effect size yang diperoleh dari random effect. Adapun meta-analisis yang digunakan dalam penelitian ini menggunakan metode Egger’s Regression. Perhitungan menggunakan software jamovi versi 2.2.5.0 untuk melakukan proses perhitungan data. Hasil penelitian menunjukkan bahwa nilai random effect model yaitu sebesar -1,24 (95% CI= -2,249 hingga -0,227). Hasil dari nilai p value = <0,001 dengan nilai I² (inconsistency)= 98,67%. Berdasarkan hasil uji meta-analisis dapat disimpulkan bahwa ACT menunjukkan adanya effect size yang besar. Hai ini menunjukkan berarti intervensi ACT memiliki efektifitas pada penurunan stres seseorang. Acceptance and Commitment Therapy (ACT) dapat digunakan secara efektif dan berdampak signifikan untuk menurunkan stres.